Manganese-Enhanced Magnetic Resonance Imaging for Early Detection and Characterization of Breast Cancers - Mosa Alhamami; Reza Bayat Mokhtari; Tameshwar Ganesh; Joris Tchouala Nofiele; Herman Yeger; Hai-Ling Margaret Cheng (Molecular Imaging)
Very early cancer detection is the key to improving cure. Our objective was to investigate manganese (Mn)-enhanced magnetic resonance imaging (MRI) for very early detection and characterization of breast cancers. Eighteen NOD scid gamma mice were inoculated with MCF7, MDA, and LM2 breast cancer cells and imaged periodically on a 3 T scanner beginning on day 6. T 1 -weighted imaging and T 1 measurements were performed before and 24 hours after administering MnCl 2 . At the last imaging session, Gd-DTPA was administered and tumors were excised for histology (hematoxylin-eosin and CD34 staining). All mice, except for two inoculated with MCF7 cells, developed tumors. Tumors enhanced uniformly on Mn and showed clear borders. Early small tumors (# 5 mm 3 ) demonstrated the greatest enhancement with a relative R 1 (1/T 1 ) change of 1.57 ± 0.13. R 1 increases correlated with tumor size ( r = −.34, p − .04). Differences in R 1 increases among the three tumor subtypes were most evident in early tumors. Histology confirmed uniform cancer cell distribution within tumor masses and vasculature in the periphery, which was consistent with rim-like enhancement on Gd-DTPA. Mn-enhanced MRI is a promising approach for detecting very small breast cancers in vivo and may be valuable for very early cancer detection.